Publicness-privateness - Splichal, Slavko (Javnost (Ljubljana), 2018)
A major feature of internetisation and internet-based hybrid modes of communication is the liquefaction of the boundary between publicness and privateness. For the first time in history, the mutual determinacy of publicness and privateness has been materialised within a single technological platform. The permeability of formerly solid boundaries between specific domains of human life regulated by specific regimes raises important questions of who, and how, (re)creates publicness and privateness, and with what social consequences. This article discusses how the traditional concepts of publicness and privateness need to be reconceptualised to capture changes in the public and private modes of relationships among people created in and by internetisation, and to explore affordances and constraints of integrated public-private communication networks for people's democratic political engagement.
Keywords: Communication; Democracy; Demokracija; Internet; Javnost; Komuniciranje; Privacy; Public; Zasebnost